Impact of Dental Treatment under General Anaesthesia on Oral Health-related Quality of Life, Weight and Oral Hygiene Measures in Children: A Quasi-experimental Study - Khlood Baghlaf; Haneen Baty; Ibtesam Alzain; Akram Qutob; Medhat Abdulla (Journal of Clinical and Diagnostic Research)
Introduction: Dental treatment for children who cannot be controlled by standard behaviour management strategies or who are unable to endure more advanced pharmaceutical approaches is challenging. Dental treatment under General Anaesthesia (GA) is suitable for these uncooperative children. There is a gap in the literature regarding whether dental treatment under GA is associated with changes in weight and oral hygiene measures. Aim: To evaluate children’s Oral Health-related Quality of Life (OHRQoL) and the changes in weight, dental history, dental pain, and oral hygiene measures after dental treatment under GA. Materials and Methods: The present pretest-post-test quasi-experimental study involving children aged 3-6 years scheduled for dental treatment under GA was conducted in the Department of Paediatric Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia, from September 2022 to December 2023. A convenience sampling method was used, with a total of 93 children participating. A validated measure was employed to assess OHRQoL. Additionally, weight, dental history, dental pain and oral hygiene measures were assessed before and after dental treatment under GA. A follow-up visit was scheduled six weeks after the GA. Data were entered and analysed using Statistical Package for Social Sciences (SPSS) software version 22.0 Statistics for Windows. Results: The mean±Standard Deviation (SD) age of the children in the current study was 4.88±1.06 years. The findings showed a significant improvement in OHRQoL after dental treatment under GA. The mean±SD score of the total OHRQoL before dental treatment was 15.73±10.2. The mean±SD score after GA was 6.64±8.52 (p-value<0.001). The mean±SD weight of the children before GA was 16.72±3.17, and six weeks after dental treatment under GA, the mean±SD weight was 16.99±3.73, with no statistically significant difference (p-value=0.21). The findings also indicated an improvement in oral hygiene practices among children after dental treatment under GA. Conclusion: Dental treatment under GA improves OHRQoL in children. No significant difference was found concerning weight change after six weeks of dental treatment. An improvement in oral hygiene practices was observed following dental treatment under GA.